2018
DOI: 10.1016/j.cell.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of the Fruit Metabolome in Tomato Breeding

Abstract: Humans heavily rely on dozens of domesticated plant species that have been further improved through intensive breeding. To evaluate how breeding changed the tomato fruit metabolome, we have generated and analyzed a dataset encompassing genomes, transcriptomes, and metabolomes from hundreds of tomato genotypes. The combined results illustrate how breeding globally altered fruit metabolite content. Selection for alleles of genes associated with larger fruits altered metabolite profiles as a consequence of linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
735
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 694 publications
(754 citation statements)
references
References 66 publications
(72 reference statements)
13
735
1
5
Order By: Relevance
“…To demonstrate the universal applications of HTPmod in data exploration and visualization, we provided various example data sets from recent studies (Supplementary Table 3) spanning phenomics 1,25,27 , metabolomics 41 , epigenomics 37 , regulatomics 21,26 and transcriptomics 42 . We explored these data using the various functionalities implemented in our HTPmod system (see also online application for demonstrations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the universal applications of HTPmod in data exploration and visualization, we provided various example data sets from recent studies (Supplementary Table 3) spanning phenomics 1,25,27 , metabolomics 41 , epigenomics 37 , regulatomics 21,26 and transcriptomics 42 . We explored these data using the various functionalities implemented in our HTPmod system (see also online application for demonstrations).…”
Section: Resultsmentioning
confidence: 99%
“…In order to demonstrate that HTPmod is powerful for modeling and visualization of large-scale biological data in different contexts, we provided several case studies ranging from genomics to phenomics 1,21,25–27,37,41,42 (Supplementary Table 3) and have shown that HTPmod is an easy-to-use tool that generates reproducible results in a very efficient way. Compared to existing analysis protocols 38,43,44 , HTPmod offers several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…As a resource of selective pressures, human behavior in crop improvement also affected the metabolic evolution (Zhou et al ., ; Zhu et al ., ). For instance, humans have selected for less bitter fruit during tomato breeding, consequently reducing the content of the bitter compounds (Zhu et al ., ).…”
Section: The Rise Of Metabolic Diversitymentioning
confidence: 97%
“…To identify effects of more widespread genetic variants on metabolic diversity across natural populations, mGWAS was initially applied in the model species Arabidopsis thaliana and then successfully performed in and extended to a number of other species, especially important crops. These studies covered primary metabolites (Strauch et al ., ; Angelovici et al ., ; Du et al ., ) and secondary metabolites (Dong et al ., ; Peng et al ., , ), ranging from vegetative tissue (Chen et al ., ; Matsuda et al ., ; Fang et al ., ) to reproductive tissue (Wen et al ., ; Zhou et al ., ; Zhu et al ., ). Generally, agricultural performance is under the control of numerous loci of small effects (Huang et al ., ).…”
Section: Deciphering the Genetic Bases Of Metabolic Diversity With Mgwasmentioning
confidence: 97%
“…More recently, Zhu et al . () performed transcriptome‐based association mapping in a collection of 399 diverse tomato genotypes and identified 2566 cis eQTLs and 93 587 trans eQTLs involved in the expression level variations of 3465 genes. QTL‐by‐watering regime interactions were recently reported for tomato fruit quality traits, emphasizing their importance for its improvement (Gur et al ., ; Albert et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%